Kewirausahaan Sosial sebagai Solusi Inovatif untuk Mengatasi Masalah Kemiskinan di Pedesaan - Sulung Anom; Yayan Hendayana (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
Poverty in rural Indonesia is higher compared to urban areas where around 12.82% of rural residents live below the poverty line. Rural communities are often unable to exploit existing economic potential due to lack of access to markets, technology and adequate infrastructure. This study aims to analyze the role of social entrepreneurship in addressing poverty in rural areas of Indonesia through a literature review method. Social entrepreneurship is viewed as an innovative solution that not only focuses on financial profit but also on social impact, empowering rural communities, creating jobs, and improving living standards. Based on the review of 9 relevant journals, the study found that social entrepreneurship in rural areas can increase income by utilizing local potential such as agricultural products and handicrafts. However, the main challenges faced include limited infrastructure, access to technology, and insufficient skill training for rural communities. Therefore, to achieve significant impact, social entrepreneurship requires clear policy support, adequate training, and the development of social capital at the community level. This study concludes that social entrepreneurship holds great potential in reducing poverty in rural areas, but it requires an inclusive and integrated approach to provide long-term benefits for rural communities.